Different applications of concept maps in higher education - Amparo Bes-Piá; Blasco Tamarit Encarna; María José Mu\~noz-Portero (Journal of Industrial Engineering and Management (JIEM), 2011)
Purpose: The aim of this work is to show different applications of concept maps in higher education, concretely in qualifications of the Polytechnic University of Valencia. Design/methodology/approach: Different methodologies have been used depending on the application of concept maps: as evaluation tool, as knowledge organizing tool, and as meaningful learning tool. Findings: Students consider the concept maps useful principally to select key ideas, to achieve a comprehensive view of the lesson, and to bring up the subject. Moreover, concept maps promote the meaningful and active learning, help students to understand, follow-up, and learn subjects with a high load of contents. Research limitations/implications: The most important limitation is the use of the concept maps in subjects with a high number of students. Practical implications: The realization of concept maps allows the student to develop generic competences. Originality/value: The originality of this work is to show how a same tool can be used in different subjects of different qualifications.
Keywords: 650; concept map; evaluation tool; knowledge organizing tool; meaningful learning